The Humid and Subhumid Tropics - ter Kuile, Coenrad H. H. (International Food Policy Research Institute, 1987)
The humid and subhumid tropics in African regions where rainfall exceeds potential evapotranspiration for five months or more include most of the area from Guinea through central Africa plus the southern part of East Africa. They cover 12 million square kilometers, or 43 percent of the total land area, and include the humid forest zone of central Africa. Rainfall is over 1 thousand millimeters per annum. Regimes prevalent in these zones are monomodal in the derived savannas, with four to six humid months; bimodal in the transition zones of the tropical forest region, with a major cropping season of four months and a minor season of about two and a half months; and pseudobimodal in the wetter forest regions, with seven to nine or more humid months.